2016
DOI: 10.1038/tp.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal anxiety during pregnancy on IGF2/H19 methylation in cord blood

Abstract: Compelling evidence suggests that maternal mental health in pregnancy can influence fetal development. The imprinted genes, insulin-like growth factor 2 (IGF2) and H19, are involved in fetal growth and each is regulated by DNA methylation. This study aimed to determine the association between maternal mental well-being during pregnancy and differentially methylated regions (DMRs) of IGF2 (DMR0) and the IGF2/H19 imprinting control region (ICR) in newborn offspring. Maternal depression, anxiety and perceived str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 59 publications
0
41
0
2
Order By: Relevance
“…For example, recent analyses in the Lifestyle and environmental factors and their Influence on Newborns Allergy risk (LINA) study reported differentially methylated regions in calcium- and Wnt-signaling pathways involved in lung maturation prenatally among children exposed to increased prenatal stress who went on to develop wheeze 54 . Other evidence indicates that stress-induced epigenetic changes that influence development can be sex specific 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent analyses in the Lifestyle and environmental factors and their Influence on Newborns Allergy risk (LINA) study reported differentially methylated regions in calcium- and Wnt-signaling pathways involved in lung maturation prenatally among children exposed to increased prenatal stress who went on to develop wheeze 54 . Other evidence indicates that stress-induced epigenetic changes that influence development can be sex specific 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in a subset of samples ( n = 158) higher cord blood MEG3 methylation was associated with internalizing behaviors of 1‐year‐old infants (Fuemmeler et al, ). Also, a later study showed association between maternal anxiety, depression, perceived stress, and decreased methylation at the IGF2/H19 locus in 576 neonatal cord blood samples (Mansell et al, ). Interestingly, both studies observed stronger effects in female infants.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
“…For example, maternal depression in the third trimester of pregnancy has also been associated with altered methylation of NR3C1 gene promoter regions in cord blood mononuclear cells, and this corresponded to altered stress responses in the three month old infants [35]. Altered DNA methylation of other gene regions has also been reported with maternal anxiety, including changes in the imprinting control region of IGF2/H19 [38]. Additional analyses of these data showed that when segregated by birth weight, the relationship between DNA methylation and maternal anxiety was stronger in the lower birthweight group (≤3530 g) and when stratified by sex, the relationship was only seen in females [38].…”
Section: Dna Methylation Biomarkers Of Neurodevelopment Outcomementioning
confidence: 99%
“…Altered DNA methylation of other gene regions has also been reported with maternal anxiety, including changes in the imprinting control region of IGF2/H19 [38]. Additional analyses of these data showed that when segregated by birth weight, the relationship between DNA methylation and maternal anxiety was stronger in the lower birthweight group (≤3530 g) and when stratified by sex, the relationship was only seen in females [38]. Together, studies in humans and rats demonstrate that maternal mental health and behavior towards her offspring in very early life can result in epigenetic modifications, which appear to increase vulnerability to poor long term neurodevelopmental outcomes.…”
Section: Dna Methylation Biomarkers Of Neurodevelopment Outcomementioning
confidence: 99%